Clinical Biology and Potential Use of Thrombopoietin - Russell Basser (Canadian Journal of Gastroenterology)
The discovery of platelet growth factors raised expectations that an effective method for abrogating thrombocytopenia would soon be available in the clinic. The cytokines initially described were pleiotropic in nature, and stimulation of platelet production was generally modest. However, one of these agents, interleukin-11, was successfully shown to reduce the incidence of severe thrombocytopenia in patients receiving dose-intensive chemotherapy, and has now received approval from the United States Food and Drug Administration for this purpose. Initial clinical trials of thrombopoietin, the central regulator of megakaryocytopoiesis and thrombopoiesis, and its analogues showed these agents to be the most potent stimulators of thrombopoiesis and to be associated with few adverse effects. They have also been shown to enhance platelet recovery after chemotherapy, but early results from trials investigating their ability to prevent severe thrombocytopenia associated with the treatment of leukemia and bone marrow transplantation have been disappointing. In addition, subcutaneous administration of one of these agents, megakaryocyte growth and development factor, has been shown to induce the formation of antibodies that neutralize native thrombopoietin and cause thrombocytopenia. Platelet growth factors remain promising therapeutic agents; however, there are a number of obstacles to overcome before they find general use in the clinic.